2018
DOI: 10.1111/inm.12465
|View full text |Cite
|
Sign up to set email alerts
|

Are Australian smokers with mental illness receiving adequate smoking cessation and harm reduction information?

Abstract: Provision of smoking cessation support in the form of advice and information is central to increasing quit rates, including among people with mental illness (MI), who have 3-5 times higher odds of smoking than those without MI. This study investigated the extent and perceived utility of quit smoking advice and information available to Australian smokers with MI through face-to-face, semi-structured, in-depth interviews with 29 current smokers with MI. Qualitative analysis identified four major sources of quit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“… 33 GPs are seen as important because they can provide practical and emotional support, 10 but some smokers with mental health conditions have indicated that they are not getting adequate support from these services. 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 GPs are seen as important because they can provide practical and emotional support, 10 but some smokers with mental health conditions have indicated that they are not getting adequate support from these services. 34 …”
Section: Discussionmentioning
confidence: 99%
“…33 GPs are seen as important because they can provide practical and emotional support, 10 but some smokers with mental health conditions have indicated that they are not getting adequate support from these services. 34 This study has some limitations. The 'method of quit attempt' question with pre-specified response options was designed to capture broad trends in preferences among smokers rather than detailed insights into individual smoking cessation strategies over time or the likelihood of success from each of the methods that were trialed.…”
Section: Assisted Cessationmentioning
confidence: 91%
“…This study is the second of a two-stage project. The first stage investigated the availability and perceived utility of quit smoking advice among 29 Australian smokers living with MI (Sharma-Kumar et al, 2018). The second stage, reported here, describes these participants' perceived acceptability and effectiveness of example videos promoting smoking cessation developed specifically for people living with MI.…”
Section: Methodsmentioning
confidence: 99%
“…The 10-item Kessler Psychological Distress Scale (K10) was also included, 29 which asked all participants about their emotional states in the past four weeks with a five-level response scale (from 1 = 'none of the time' to 5 = 'all of the time'). Based on their responses to the ten items, participants' overall level of psychological distress was categorised as low (score range 10-15), moderate (16)(17)(18)(19)(20)(21), high (22)(23)(24)(25)(26)(27)(28)(29) or very high .…”
Section: Mental Health Statusmentioning
confidence: 99%
“…13 Although smokers with mental illness have lower rates of smoking cessation, 6,14 such smokers appear to be just as motivated to quit as the general population, 6,15 and are able to achieve long-term cessation. 16 Despite this, smokers with mental illness report a lack of encouragement to quit by health professionals, 17 who are subject to a range of competing priorities and other systemic barriers, 18 and who may mistakenly believe that people with mental illness are not interested in quitting and that it will interfere with their mental health recovery. 19 Such beliefs, combined with a lack of training, experience, or confidence, 20 can act as significant barriers to providing cessation support.…”
mentioning
confidence: 99%